Effect of Self-Healing Calcium Nitrate Microcapsules on Concrete Properties. Issue 1 (2016) - Milla, Jose; Hassan, Marwa M.; Rupnow, Tyson; Al-Ansari, Mohamed; Arce, Gabriel
Self-healing concrete with microencapsulated calcium nitrate was investigated. The compressive strength of concrete admixed with microcapsules (as a percentage of the weight of the cement) was tested and compared with that of control specimens of the same mix design without microcapsules. Surface resistivity tests were conducted to quantify the surface permeability of the concrete specimens with and without microcapsules. The self-healing potential was measured by the modulus of elasticity test (ASTM C469), with measurements being taken before and after damage after 14 days. After the concrete was damaged by application of 80% of its ultimate load, all specimens were incubated by immersion in water. The results showed that the concentration of microcapsules added and the size of the microcapsules had a direct impact on the compressive strength of the concrete. Furthermore, the concrete specimens into which microcapsules were incorporated had greater surface resistivity than the control specimens. The recovery of the modulus of elasticity was analyzed according to the increase from the modulus of elasticity recorded after application of 80% of the sample's ultimate load and the increase relative to the initial modulus of elasticity of the concrete in the virgin state. Overall, the results of this study indicated that although microcapsules caused a decrease in the compressive strength of the concrete, they enhanced the self-healing capability of the concrete that was produced. To take advantage of the benefits of microcapsules, the authors recommend that future work evaluate the use of a dispersing agent to reduce the amount of microcapsules needed in the mix.